Comparison of kinematic characteristics between standing and rotational discus throws - Nemtsev, O. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to describe the differences of kinematic characteristics of movements of the arm with a discus in delivery phase between standing and rotational discus throws. For this purpose, four male throwers performed three standing discus throws and three rotational throws. All trials were high-speed videotaped. The results of 3-D analysis indicated that discus descends lower and its release angle is less in standing throw.